Parenting and infant cry - Esposito, Gianluca (2019)
This Special Issue collects five empirical studies from around the world that use diverse methodological approaches and focus at different levels to investigate how behavioral, hormonal, prenatal and postnatal factors, brain functioning, and environment regulate early interactions of parents with distressed infants and young children.